O ensino de língua portuguesa e os projetos de letramento: uma proposta de atividades com foco na questão alimentar a partir do gênero anúncio de campanha comunitária - Souza, Francisco Ernandes Braga de (2017)
In recent years, the discussions about the development of literacy projects have expanded immensely. Those discussions contemplate concerning the contributions of the literacy projects, on behalf of reading activities and production of text contextualized and located with the students' reality. The present work has as general objective to introducer on the contributions of the projects of literacies for the teaching of Portuguese Language for the teaching of Portuguese Language in classroom of the 5th year of the Fundamental Teaching I, in a municipal school of the city of Itapissuma-PE. As specific objectives, we intend to: to reflect on the use of literacy projects, with the purpose of carrying out didactic activities engaged with the students' daily problems; propose the realization of a literacy project, focusing on the food problem, more specifically, in promoting healthy eating; propose a sequence of activities, aiming to work on reading practices, written and oral text production, using the announcement of community campaign. For accomplishment of those objectives, we anchored ourselves in the contributions of the research action, as well as in the literature review and in the application of a sequence of activities. The results demonstrate that the students' productions assisted to the constituent characteristics of the gender announcement of community campaign. Even with daily and simple resources (pens hydrographic, newspapers, magazines etc.), the students' productions got to reproduce differentiated characteristics of that discursive and textual gender. In that sense, this work articulated a literacy project and the subsidies of the gender community campaign announcement, causing a significant incentive to the political engagement and the students' participatory, in what concerns the context in that you/they live. It is with that glance that we considered the use of literacy projects in the teaching of Portuguese Language as something of extreme relevance, once it will motivate the student's potential in the involvement of his/her reality, aiming at the intervention and the transformation.